2017
DOI: 10.14740/cr542w
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Appendage Volume and Plasma Docosahexaenoic Acid Levels Are Associated With Atrial Fibrillation Recurrence After Catheter Ablation

Abstract: BackgroundRisk factors for atrial fibrillation (AF) recurrence in patients who have undergone AF catheter ablation have not been fully clarified. The objective of this study was to assess whether the left atrium (LA) and LA appendage (LAA) volumes, and cardio-metabolic markers such as polyunsaturated fatty acids (PUFAs) levels were associated with AF recurrence.MethodsSeventy-seven consecutive patients with AF (mean age, 59 ± 8 years; male, 81%; paroxysmal AF, 64%) undergoing catheter ablation were enrolled. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…Table 1 displayed the study characteristics of 16 included studies, comprising 9 ( 12 , 15 , 18 , 20 , 21 , 23 25 , 27 ) prospective studies and 7 ( 13 , 14 , 16 , 17 , 19 , 22 , 26 ) retrospective studies. Six studies ( 19 , 22 25 , 27 ) were conducted in China, 4 studies ( 15 , 16 , 20 , 21 ) in Japan, 2 studies ( 14 , 17 ) in Hungary, 1 study ( 26 ) in South Korea, 1 study ( 13 ) in Poland, 1 study ( 12 ) in Türkiye, and 1 study ( 18 ) in Romania. Sixteen studies with 5,006 AF patients after CA (1,479 patients with AF recurrence, 3,527 without AF recurrence) were included, and the proportion of AF patients with recurrence ranged from 24.1 to 41.5%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 displayed the study characteristics of 16 included studies, comprising 9 ( 12 , 15 , 18 , 20 , 21 , 23 25 , 27 ) prospective studies and 7 ( 13 , 14 , 16 , 17 , 19 , 22 , 26 ) retrospective studies. Six studies ( 19 , 22 25 , 27 ) were conducted in China, 4 studies ( 15 , 16 , 20 , 21 ) in Japan, 2 studies ( 14 , 17 ) in Hungary, 1 study ( 26 ) in South Korea, 1 study ( 13 ) in Poland, 1 study ( 12 ) in Türkiye, and 1 study ( 18 ) in Romania. Sixteen studies with 5,006 AF patients after CA (1,479 patients with AF recurrence, 3,527 without AF recurrence) were included, and the proportion of AF patients with recurrence ranged from 24.1 to 41.5%.…”
Section: Resultsmentioning
confidence: 99%
“…The mean age ranged from 54.6 ± 10.4 to 67.5 ± 7.5 years, and the median follow-up time varied from 6 to 48 months. Nine ( 12 15 , 17 , 18 , 22 , 23 , 25 ) studies performed circumferential pulmonary vein isolation (CPVI) alone, whereas 7 ( 16 , 19 21 , 24 , 26 , 27 ) studies conducted additional linear ablations. The LAAFV, which refers to the peak flow emptying velocity of the left atrial appendage at late diastole, was measured by transthoracic echocardiography (TEE) in all selected research.…”
Section: Resultsmentioning
confidence: 99%
“…For the LAA volume, He et al demonstrated in a study with transesophageal echocardiography for measuring the LAA volume and function that the LAAVmax and LAAVmin were markedly increased in recurrence while the function parameters including LAAEF, LAA flow emptying velocity and summit filling velocity were significantly decreased, with the multivariate analysis showing the left atrial volume index, LAAEF and LAA flow emptying velocity to be significant factors to predict paroxysmal AF recurrence following radiofrequency ablation 21 . In a study with multi-detector CT scanning investigating the LAA volume in association with AF recurrence following radiofrequency ablation 22 , Shiozawa et al found that both greater LAA volumes and orifice areas were exhibited in recurrent AF patients while the diameter and volume of the left atrium did not have significant differences between patients with and without recurrence. All patients possessing a LAA volume greater than 25 ml experienced AF recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…All patients possessing a LAA volume greater than 25 ml experienced AF recurrence. As an embryonic remnant of the left atrium, the LAA plays a very important role in adjusting heart rate and fluid balance via an expandable reservoir function, a capacity to secret atrial natriuretic peptides, and sensitive receptors of stretch [22][23][24] . The LAA is distensible at a greater degree than the left atrium, and the LAA volume is a dependable parameter to determine the left atrial conditions in both function and structure in early AF.…”
Section: Discussionmentioning
confidence: 99%
“…Association between LAA-PEV and AF Some studies have found that LAA is one of the potential trigger points of spontaneous AF [32]. Increased LAA volume and decreased LAA ejection fraction were predictors of recurrence after ablation of AF [33][34][35][36]. The decrease in LAA-PEV was positively correlated with postoperative recurrence of AF [37].…”
Section: Association Between Laapd and Afmentioning
confidence: 99%